A Benefits Realization Management Building Information Modeling Framework for Asset Owners - Love, Peter; Matthews, Jane; Simpson, I.; Hill, A.; Olatunji, Oluwole (Elsevier BV, 2014)
An asset owner's decision to implement Building Information Modeling (BIM) can enable strategic business outcomes. For an asset owner the implementation of BIM should not be seen as a discrete information technology project, but a business change program that can potentially impact their ‘value proposition’. Benefits realization recognizes that technology alone cannot deliver business outcomes and that the process of its implementation is proactively managed to ensure that the organization obtains the results it expects. This paper presents a novel framework that asset owners can use to ensure that they can obtain ‘value’ from investing in BIM. It is profferedthat the benefits realization process should be viewed as a learning process that enables the asset owner to constantly question and measure the benefits of BIM.